“I am always tired”: Perceptions on Mental Health and Productivity Metrics - Azevedo, Júlia; Sousa, Theo; Arriel, Johny; Mann, Paulo; Garcia, Alessandro; Pereira, Juliana Alves (Anais Estendidos do Congresso Brasileiro de Software: Teoria e Prática (CBSoft), 2024)
This study aims to gather insights from tech and health professionals regarding their perceptions about twelve proposed metrics designed to measure mental health and productivity in software development. These professionals were surveyed to rate the usefulness and appropriateness of each proposed metric. The findings offer valuable insights into the factors that influence the perceived utility and likability of these metrics. By leveraging developers perceptions, we can develop more effective strategies to promote a healthier and more productive work environment in software development. Thus, this study paves the way for the implementation of more targeted interventions and best practices within the industry.